2021
DOI: 10.33503/prismatika.v4i1.1441
|View full text |Cite
|
Sign up to set email alerts
|

Eksplorasi Konsep Dilatasi Etnomatematika Pada Batik Tembakau Jember

Abstract: Etnomatematika merupakan ragam cara yang berbeda dalam melakukan matematika yang memperhitungkan penggunaan konsep-konsep matematika dalam sistem akademik yang dikembangkan di berbagai lapisan masyarakat dengan tetap memperhatikan tujuan yang berbeda – beda, dimana perbedaan budaya akan menciptakan perbedaan dalam praktek matematikanya (cara berhitung, mengelompokkan, mengukur, merancang bangunan atau alat, bermain dan lainnya). Berdasarkan hal tesebut  penelitian ini bertujuan  mendeskripsikan hasil eksploras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Answer the Question curved lines, the Gentongan batik motif includes the straight lines, rhombuses, and angles, the Tanjung Bumi batik motif contains parallel lines, the Bangkalan batik motif incorporates congruence and triangles, the Simple batik motif features points and symmetry, and the Sampang batik motif includes circles. (Sulisawati et al, 2021) The results of this study showed that the tobacco batik from Jember incorporates a mathematical concept known as geometric transformation, specifically dilation.…”
Section: Research Resultsmentioning
confidence: 86%
“…Answer the Question curved lines, the Gentongan batik motif includes the straight lines, rhombuses, and angles, the Tanjung Bumi batik motif contains parallel lines, the Bangkalan batik motif incorporates congruence and triangles, the Simple batik motif features points and symmetry, and the Sampang batik motif includes circles. (Sulisawati et al, 2021) The results of this study showed that the tobacco batik from Jember incorporates a mathematical concept known as geometric transformation, specifically dilation.…”
Section: Research Resultsmentioning
confidence: 86%